Enhanced thermal conductance at the graphene–water interface based on functionalized alkane chains. Issue 8 (6th February 2019) - Chen, Shuyu; Yang, Ming; Liu, Bin; Xu, Min; Zhang, Teng; Zhuang, Bilin; Ding, Ding; Huai, Xiulan; Zhang, Hang
Abstract : This work demonstrates an effective and universal method to improve thermal transport properties on the interface between multilayer graphene and water by a factor of ~4 via grafting functionalized groups on graphene. Abstract : Highly efficient thermal transport between graphene and water is crucial in applications such as microscopic heat dissipation, solar steam generation, sea-water desalination, and thermally conductive composites. However, a practical approach for enhancing thermal transport across graphene–water interfaces is lacking. We propose an effective and universal method to improve thermal-transport properties at the interface between multilayer graphene and water by a factor of ∼4 by grafting functionalized groups onto graphene. The most improved interfacial thermal conductance was 121.0 ± 11.4 MW m −2 K −1 . This design is compatible with industrial processes. We also undertook molecular-level analyses to unveil the underlying mechanism for heat-transport enhancement. This study could provide new approaches for engineering heat transport across two-dimensional materials and water interfaces.